Polymorphism of Mitogen-activated protein kinase 12 (MAPK12) gene in Vechur and Kasargod cattle of Kerala - T.X. Seena; Elizabeth Kurian; F.A. Lali; P.M. Rojan; K.A. Bindu; Aziz Zarina; K. George Sherin (Journal of Veterinary and Animal Sciences, 2025)
The mitogen-activated protein kinase 12 (MAPK12) gene, located on chromosome 5 of the cattle genome and consists of 12 exons. This gene plays a crucial role in sphingolipid signalling and Wnt signalling pathways, both of which are associated with thermo-tolerance in cattle. This study was conducted to investigate genetic polymorphisms in the MAPK12 gene in Vechur and Kasargod, the native, dwarf cattle of Kerala. They are known for their disease resistance, resilience to biotic and abiotic stresses and their ability to thrive under limited feed resources in varied agro-climatic conditions of the state. A missense mutation (GA) was identified in exon 8 of the MAPK12 gene at 119621852bp position by genotyping using High-Resolution Melting (HRM) analysis. The genotyping revealed AA and GA genotypes as distinct clusters in plots. The frequency of the AA genotype was the highest in both Vechur (0.91) and Kasargod cattle (0.79). Chi-square analysis indicated that both populations were in Hardy-Weinberg equilibrium (HWE) (p0.05). Structural annotation of the variation in MAPK12 protein was examined by various computational tools, which indicate that the SNP lead to structural conformational changes in the protein structure when compared to the wild-type MAPK12 protein